Behind and Beyond the Masaoka Staging: A 25-Year Follow-up Study of Tumor Recurrence in Completely Resected Thymic Epithelial Tumors in a Single Institution. Issue 52 (December 2015) - Tseng, Yau-Lin; Chang, Jia-Ming; Lai, Wu-Wei; Chang, Kung-Chao; Lee, Shang-Chi; Lin, Sheng-Hsiang; Yen, Yi-Ting
Abstract : Abstract: We analyzed prognosticators for recurrence and post-recurrence survival in completely resected thymic epithelial tumors for the past 25 years in a single institution. Between June 1988 and December 2013, 238 patients undergoing intent-to-treat surgery for thymic epithelial tumors were reviewed. Sex, age, myasthenia gravis (MG), tumor histology, Masaoka staging, characteristic of locoregional invasion and recurrence, and the treatment for recurrence were collected. Comparison between groups was conducted using the Student t test and χ 2 test. Survival analysis was performed using the Kaplan–Meier method and log-rank test. The Cox proportional hazards model was used for univariate and multivariate analyses of prognostic factors. One hundred sixteen of 135 patients with completely resected thymoma and 35 of 56 patients with thymic carcinoma remained free of recurrence. In patients with completely resected thymoma, Masaoka staging, MG, tumor invasion into the lung, pericardium, and innominate vein or superior vena cava (SVC) invasion were associated with recurrence-free survival in univariate analysis ( P  = 0.004, 0.003, 0.001, 0.007, and 0.039, respectively). In multivariate analysis, MG was the positive independent prognosticator ( P  = 0.039). In patients with completely resected thymic carcinoma, Masaoka staging and innominate vein or SVC invasion were associated with recurrence-free survival in univariate analysis ( P  = 0.045 and 0.005, respectively), whereas innominate vein or SVC invasion was the negative independent prognosticator ( P  = 0.012). In patients with recurrent thymoma, those treated with surgery followed by chemotherapy had a significantly better post-recurrence survival than those undergoing chemoradiotherapy ( P  = 0.029) and those without treatment ( P  = 0.007). Patients with recurrent thymic carcinoma undergoing surgery followed by chemotherapy had a significantly better post-recurrence survival than those without treatment ( P  = 0.004), but not significantly better than those undergoing chemoradiotherapy ( P  = 0.252). In patients with completely resected thymoma, MG was the positive independent prognosticators of recurrence-free survival. Surgery should be attempted for recurrent disease for better post-recurrence survival. In patients with completely resected thymic carcinoma, innominate vein or SVC invasion was the negative independent prognosticator. Surgery for recurrence could be considered since it provided benefit for post-recurrence survival as chemoradiotherapy did.